PROFIL SOFT SKILL MAHASISWA PADA MATA KULIAH PENGEMBANGAN PROGRAM PEMBELAJARAN BIOLOGI TAHUN AKADEMIS 2010/2011 - Mariani Natalina L; Evi Suryawati; Susi Susanti (Biogenesis, 2011)
Research had been taken to see Student’s Soft Skill Profile of University on Developing Biology Education Program Lecture, on 2010/2011 Academic Year, through March until June 2011. Total Sample for this research is all of the students on the University who were taking Developing Biology Education Program Lecture that consist of 43 students (40 students are female and 3 students are male). Parameter of this research is Soft Skill describe in 7 indicators which are creativity, self-confidence, independent, motivation, critical thinking, time management and team-work. Instruments that were used are Soft Skill score base on the process using the all of seventh soft skill indicators and scoring work performance using 2 indicators from all of seventh Soft Skill. The result of the research shows Soft Skill score base on process is average 67.26% (enough). On RPP and LKS process the average score 65.41% (enough), on Mikro Education average score 62.94% (enough), on media presentation process average score 75.29% (good), and from all of the seventh Soft Skill indicators, the highest score is team-work indicator with average 88% (very good), whereas the lowest score is critical thinking indicator with average score 68% (enough). Soft Skill Profile score on team-work indicator is average 73.72% (enough), on the RPP work performance is 60.91% (enough score), on the LKS is 62.80% (enough), on educative media 85.79% (very good), on teaching material is 85.40% (very good), among two Soft Skill indicators the highest score is critical thinking indicator whose score is 74.19% (enough), meanwhile, the lowest score is creativity with score 73.26% (enough). By totally, Soft Skill Profile of university student score base on process and work performance on Developing Biology Education lecture is 70.49% within enough category.Keywords : Education Program, Soft Skill,